Stationary Navier–Stokes equations with non-homogeneous boundary condition in the unbounded domain - Kaulakytė, Kristina (Lietuvos matematikos rinkinys, 2011)
In this paper the stationary Navier–Stokes system with non-homogeneous boundary condition is studied in the unbounded domain. The extension of the boundary value satisfying Leray’s inequality is constructed. Therefore the non-homogeneous boundary problem could be reduced to the homogeneous one which was already investigated before.